Phytochemical properties of plant species of the Campanulaceae family (Development Engineering Conferences Center Articles Database, 2025)
The Campanulaceae family, which encompasses approximately 40 genera and 600 species, serves as a substantial reservoir of medicinal plants that are extensively utilized in both traditional and contemporary healthcare modalities. Phytochemical research has elucidated those constituents of this family, particularly those within the genus Codonopsis, harbor a plethora of bioactive compounds including polyacetylene, phenylpropanoids, alkaloids, triterpenoids, flavonoids, and polysaccharides, which underpin their extensive pharmacological effects (Dimitriadis et al., 2024; He et al., 2015).Prominent medicinal attributes ascribed to plants within the Campanulaceae family encompass antioxidant, anti-inflammatory, immunomodulatory, anticancer, adaptogenic, and antimicrobial properties (Dimitriadis et al., 2024; Gao et al., 2018; Liu et al., 2024).For example, Codonopsis pilosula and allied species are distinguished for their roles in enhancing immune function, modulating metabolic processes, and demonstrating anti-tumor efficacy through mechanisms such as the induction of apoptosis and the suppression of cancer cell proliferation (Bailly, 2020; Liu et al., 2024). Other genera, such as Campanula, have demonstrated strong antioxidant and enzyme inhibitory activities linked to their phenolic and flavonoid content (Dimitriadis et al., 2024). Despite these promising findings, further research is needed to elucidate the mechanisms of action, standardize quality control, and validate the clinical efficacy. Overall, the Campanulaceae family represents a valuable reservoir of phytochemicals with significant potential for the development of novel nutraceuticals and therapeutic agents (Dimitriadis et al., 2024; He et al., 2015; Liu et al., 2024).